Assessment of post-harvest losses and carbon footprint in intensive lowland rice production in Myanmar - Gummert, Martin; Nguyen-Van-Hung; Cabardo, Christopher; Quilloy, Reianne; Aung, Yan Lin; Thant, Aung Myo; Kyaw, Myo Aung; Labios, Romeo; Htwe, Nyo Me; Singleton, Grant R. (Springer, 2020)
This paper examines how a move from traditional post-harvest operations of smallholder rice farms in the Ayeyarwaddy delta, Myanmar, to improved post-harvest operations affected income, energy efficiency and greenhouse gas emissions (GHGE). Harvest and post-harvest losses were investigated in a field experiment with 5 replications per scenario. A comparative analysis on energy efficiency and cost-benefits was conducted for different practices of rice production from cultivation to milling. GHGE of different practices were also considered using a life-cycle assessment approach. The study demonstrates that the mechanized practices increased the net income by 30–50% compared with traditional practices. Despite using additional energy for machine manufacturing and fuel consumption, the mechanized practices significantly reduced postharvest losses and did not increase the total life-cycle enegy and GHGE. Combine harvesting helped to significantly reduce harvesting loss in a range of 3 to 7% (by weight of the rice product). Improved post-harvest management practices with a flatbed dryer and hermetic storage reduced the discoloration of rice grains by 3 to 4% and increased head-rice recovery by 20 to 30% (by weight of rice product). The research findings provide empirical evidence that improved post-harvest management of rice in the Ayeyarwaddy delta, compared to traditional post-harvest operations by smallholder farmers, reduce post-harvest losses and improve the quality of rice. The findings provide valuable information for policy makers involved in formulating evidence-based mechanization policies in South and Southeast Asia.